The radon concentrations of some waters in Bitlis (Turkey) and their dose estimates - Bal, Sultan Sahin; Tanriverdi, Erkan; Yalcin, Sezai; Dogru, Mahmut; Ozbey, Fahrettin (Springer, 2021)
The activity concentration values of Rn-222 radio-isotope, which in an alpha active isotope, were measured in Bitlis and its district water samples in this study. The samples were analyzed with AlphaGuard PQ 2000 PRO active radon measuring system. The radon values are in the range of 0.59 and 66.00 Bq/L. The annual inhalation effective dose (1.47-166.32 mu Sv/y), annual ingestion effective dose (for adults (1.50-168.63 mu Sv/y), children (1.14-128.50 mu Sv/y) and babies (0.31-34.91 mu Sv/y)), annual effective dose for stomach (for adults (0.18-20.24 mu Sv/y), children (0.14 to 15.42 mu Sv/y) and babies (0.04-4.19 mu Sv/y)), annual effective dose for lung (0.18-19.96 mu Sv/y) were estimated. The concentration level of Rn-222 in Bitlis water samples was found higher than permissible maximum value defined by Environmental Protection Agency (EPA) (11.1 Bq/L).
Keywords: Radon-222 in water; Dose calculation; Risk factor analyses; AlphaGuard; Statistic; Bitlis